2016
DOI: 10.1089/scd.2015.0389
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Increases In Vitro Survival and Proliferation and Attenuates Oxidative Stress-Induced Cell Death in Adult Spinal Cord-Derived Neural Stem/Progenitor Cells via Non-NMDA Ionotropic Glutamate Receptors

Abstract: Traumatic spinal cord injury (SCI) leads to a cascade of secondary chemical insults, including oxidative stress and glutamate excitotoxicity, which damage host neurons and glia. Transplantation of exogenous neural stem/progenitor cells (NSPCs) has shown promise in enhancing regeneration after SCI, although survival of transplanted cells remains poor. Understanding the response of NSPCs to the chemical mediators of secondary injury is essential in finding therapies to enhance survival. We examined the in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
(53 reference statements)
1
16
0
1
Order By: Relevance
“…Metabolic profiling of hippocampi ( Fig. 1G) revealed elevated levels of metabolites such as taurine, choline, glutamate, and gamma-aminobutyric acid (GABA) that regulate neurogenesis and neuromaturation (14)(15)(16)(17)(18), in old MTs compared to young MTs (Table 1). As expected, neurogenesis was lower in the old donor mice compared to the young donor mice ( Fig.…”
Section: Mice Transplanted With Microbiota From Old Donors Show Incrementioning
confidence: 99%
“…Metabolic profiling of hippocampi ( Fig. 1G) revealed elevated levels of metabolites such as taurine, choline, glutamate, and gamma-aminobutyric acid (GABA) that regulate neurogenesis and neuromaturation (14)(15)(16)(17)(18), in old MTs compared to young MTs (Table 1). As expected, neurogenesis was lower in the old donor mice compared to the young donor mice ( Fig.…”
Section: Mice Transplanted With Microbiota From Old Donors Show Incrementioning
confidence: 99%
“…The relationship between mGluRs and oxidative stress was demonstrated many years ago; however, there are relatively few studies in the literature investigating the role of mGluR2/3 in antioxidant defence. The activation of group II mGluRs has been shown to attenuate oxidative stress-induced cell death in spinal cord injury [ 14 ], protect neurons from glucose-induced oxidative injury [ 15 ], and reduce ROS production in the immature rat brain during seizures induced by a bilateral intracerebroventricular infusion of dl -homocysteic acid [ 16 ]. Recently, activation of group II mGluRs was also shown to protect against the ischemia-induced free radical programmed death of rat brain endothelial cells, although this neuroprotective effect was considered to be a complex metabotropic glutamate receptor response [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies demonstrated that high concentrations of glutamate, comparable to levels seen in vivo after SCI, lead to NSPC proliferation and enhanced survival. 31 In fact, F I G U R E 1 Cellular and genetic landscape of the spinal cord ependymal zone. Three main morphological cell types have been described within the spinal cord ependymal zone: cuboidal ependymal cells, radial ependymal cells, and tanycytes.…”
Section: Glutamate As a Positive Regulator Of Nspcsmentioning
confidence: 99%
“…32 Emerging evidence suggests that AMPA receptors may be central in regulating glutamatemediated responses in adult spinal cord NSPCs. 31,33,34 AMPA receptors are transmembrane receptors comprised of tetramers of four types of subunits: GluA1, GluA2, GluA3, and GluA4. The GluA2 subunit imparts much of the receptor's characteristics with its presence rendering the receptor impermeable to calcium.…”
Section: Glutamate As a Positive Regulator Of Nspcsmentioning
confidence: 99%